SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated p artnership approach, in contrast to the usual approach of grants to ci vil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-g rown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...